Les rapports entre politique et justice en Italie de l’après-guerre à nos jours - Alessandro Pizzorusso (Laboratoire Italien)
The author intends to trace the evolution of the relations between the political power and the magistracy in the period from post-war years to the present day. This evolution is far from being linear and univocal but it is supported by a dual intention formulated right after the Liberation: eliminating the fascist legislation and ensuring the continuity of the movement in favor of the independence of magistracy born during the liberal period. In that evolution, the independence of magistracy is seen to emerge well before the events of 1992, though the weaknesses of its institutional position are also emphasized. The author is indeed concerned with the threats that nowadays could actually jeopardize such a hard-won independence.